2019
DOI: 10.1007/978-3-030-26980-7_79
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric Algorithmic Components for Shape Analysis with Diffeomorphisms

Abstract: In computational anatomy, the statistical analysis of temporal deformations and inter-subject variability relies on shape registration. However, the numerical integration and optimization required in diffeomorphic registration often lead to important numerical errors. In many cases, it is well known that the error can be drastically reduced in the presence of a symmetry. In this work, the leading idea is to approximate the space of deformations and images with a possibly non-metric symmetric space structure us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Further work will also extend the analysis to non-linear methods, which may better preserve the structure of the data spaces associated to each descriptor. It may also include recent developments for transporting spatiotemporal shape data among a population through di↵eomorphic transformations [22], which explicitly aims at preserving the structure of the space encoding cardiac meshes.…”
Section: Resultsmentioning
confidence: 99%
“…Further work will also extend the analysis to non-linear methods, which may better preserve the structure of the data spaces associated to each descriptor. It may also include recent developments for transporting spatiotemporal shape data among a population through di↵eomorphic transformations [22], which explicitly aims at preserving the structure of the space encoding cardiac meshes.…”
Section: Resultsmentioning
confidence: 99%
“…They showed that at the first order, the constructions were equivalent. [28] latter gave a Taylor approximation of the elementary construction showing that each rung of pole ladder is a third order approximation of parallel transport, and additionally showed that PL is exact in affine (hence in Riemannian) locally symmetric spaces (the proof is reproduced in [11]). We first present the scheme and derive the Taylor approximation using the neighboring log.…”
Section: Pole Laddermentioning
confidence: 99%
“…It is not relevant to compare the PL with SL on spheres or SPD matrices as in the previous section, as theses spaces are symmetric and thus the PL is exact [11]. We therefore focus on the Lie group of isometries of R 3 , endowed with a left-invariant metric g with the diagonal matrix at identity:…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Temporal differences between sequences can also be normalized by resampling before the motion extraction [e.g., piece-wise linear interpolation (30)]. Recent approaches transport the whole subject-specific trajectory instead of the descriptors of interest, with specific computational considerations (31,32). Automatically estimating multiple templates across the sequence may also be well adapted to the cardiac circular/periodic dynamics (33).…”
Section: Before the Analysis: Data Normalizationmentioning
confidence: 99%